Mobile genetics and forms of heritable changes in eukaryotes - Golubovsky, M. (Биополимеры и клетка, 1995)
The real insight in the eukaryotic genome means knowledge of the structure of genetic elements, the character of dynamic links between them and some holistic features of the system. The structure of the eukaryotic genome can be naturally subdivided on two classes of elements: an obligatory and facultative ones. Accordingly, we need to discriminate between two different forms of heritable changes – mutations and variations. Mutations correspond to all changes with genes. Variations are various kinds of changes in the populations of genomic facultative elements. Variations may be directed and connected with multiple site specific alterations. The spontaneous mutation process in nature is mediated by the system of facultative elements. Their activation in nature induces sudden mutation outbursts, appearance of new genetic constructions and site specific rearrangements. Facultative elements are the first to react on environmental challenge. Variations can be presented as an operational memory of the genome. Between obligatory and facultative elements there is constant flow. The behavior of transposons in the eukaryotic genome may be model for the adequate description of epigenic inheritance. There is logic and real necessity to use the epigene concept for describing of elementary units of epigenetic inheritance. Реальне розуміння еукаріотичного геному означає знання структури генетичних елементів, характеру динамічного зв'язку між ними і філософії цілосності системи. Структура еукаріотичного ігеному може бути підрозділеною на два коміпоненти: облігатний і факультативний. Відповідно до цього ми повинні розрізняти дві форми спадкової мінливості – мутаційну і варіаційну. Мутації пов'язані з. усіма змінами в генах. Варіації є різними видами змін у популяціях факультативних елементів геному. Варіації можуть бути визначеними і .пов'язаними з багатьма сайт-специфічними змінами. Спонтанний мутаційний процес у природі обумовлений системою факультативних елементів їх активація у природі індукує раптові мутаційні «вибухи», появу нових генетичяих конструкцій і сайт-специфічних перебудов. Факультативні елементи першими реагують на зміни навколишнього середовища. Варіації можуть бути представлені керуючою пам'яттю геному. Між облігатними і факультативними елементами спостерігається постійна взаємодія. Поведінку транспозонів в еукаріотичному геномі можна взяти за модель для адекватного опису епігенетичної спадковості. Використання концепції епігена є логічною і реальною необхідністю для характеристики елементарних одиниць епігенетичної спадковості. Реальное понимание эукариотического генома означает знание структуры генетических элементов, характера динамической связи между ними и философии целостности системы. Структура эукариотического генома может быть подразделена на два компонента: облигатный и факультативный. Соответственно этому мы должны различать две формы наследственной изменчивости – мутационную и вариационную. Мутации связаны со всеми изменениями в генах. Вариации являются различными видами изменений в популяциях факультативных элементов генома. Вариации могут быть определенными и связаны с многочисленными сайт- специфическими изменениями. Спонтанный мутационный процесс в природе обусловлен системой факультативных элементов. Их активация в природе индуцирует внезапные мутационные -взрывы», появление новых генетических конструкций и сайт-специфических перестроек. Факультативные элементы первыми реагируют на изменения окружающей среды. Вариации могут быть представлены управляющей памятью генома. Между облигатными и факультативными элементами имеется постоянное взаимодействие. Поведение транспозоиов в эукариотическом геноме может быть моделью для адекватного описания эпигенетической наследственности. Использование концепции эпигена является логической и реальной необходимостью для характеристики элементарных единиц эпигенетической наследственности.